Why Most Research Findings About Psi Are False: The Replicability Crisis, the Psi Paradox and the Myth of Sisyphus - Rabeyron, Thomas (Frontiers in Psychology, 2020)
The replicability crisis in psychology has been influenced in particular by the results of nine experiments conducted by Daryl Bem (2011) presented as supporting the existence of precognition. In this paper we hope to show how the debate concerning these experiments could be an opportunity to develop original thinking about psychology and replicability. After a few preliminary remarks about psi and scientific epistemology, we examine how psi results lead to a paradox which questions how appropriate the scientific method is to psi research. This paradox highlights a problem in the way experiments are conducted in psi research and its potential consequence on mainstream research in psychology. Two classical experiments –the Ganzfeld protocol and the Bem studies– are then analyzed in order to illustrate this paradox and its consequences. Mainstream research is also addressed in the broader context of the replication crisis, decline effect and questionable research practices. Several perspectives for future research are proposed in conclusion and underlines the heuristic value of psi studies for psychology.